Tradisi Etnis Tionghoa dalam Bingkai Ukhuwah Islamiyah (Studi Sosiologis terhadap Tradisi Muslim Tionghoa Probolinggo) - Humaisi, M. Syafiq (FKIP Universitas Wisnuwardhana, 2022)
Islam is present in life, not only meeting with a vacuum but also its presence meeting and dealing with several traditions which are the result of human dialogue with their environment, both individually and in groups in a sociological, anthropological collectively and their trust and beliefs. The first traditions encountered by Islam were the Jahiliyah belief traditions and the traditions of the biblical experts and even the magi and Greek traditions which had been firmly rooted in life for hundreds or even thousands of years before the advent of Islam. These traditions, with sociological and anthropological integrity, become a unifying rope among the communities of human life, which are further clarified in the framework of Ukhuwah Islamiyah offered by Islam. Islam which carries the mission of a middle way, balanced, and upright, as part of the high tradition of Islam, be a blessing to the whole universe, makes what is good from these traditions continue to be perpetuated as part of the Islamic tradition. from Islamic law and what is bad is categorized as a tradition of shirk and immorality that must be avoided.